Relationship between Family Support and Nurse Caring Behavior on Compliance of Kidney Failure Patients Undergoing Hemodialysis at Undata Hospital, Central Sulawesi Province - Nurul Ilmi Syafirah; Yulta Kadang; Maryam M; Lilik Utami (An Idea Nursing Journal, 2023)
Kidney failure is a condition where kidney function declines in a few months or years, so you have to get family support and nurse caring behavior towards the compliance of kidney failure clients undergoing hemodialysis. The design used in this study was a cross sectional design, the population in the study were all respondents at the UNDATA Hospital, Central Sulawesi Province, as many as 70 respondents with the provision that the sample was according to the sample and the error was 0.10%, so the number of samples became 56. The results obtained from the relationship of family support on the compliance of renal failure clients undergoing hemodialysis. = 0.05. It was concluded that family support for the compliance of clients with kidney failure undergoing hemodialysis at the UNDATA Hospital, Central Sulawesi Province, was related. Should be able to further develop in providing support, especially for clients with kidney failure.